Volume Conduction Effects on Wavelet Cross-Bicoherence Analysis - IRFAN ALI MEMON; MUHAMMAD SIDDIQUE KALHORO; NIZAMUDDIN CHANNA (Mehran University Research Journal of Engineering and Technology, 2013)
Cross-bicoherence analysis is one of the important nonlinear signal processing tools which is used to measure quadratic phase coupling between frequencies of two different time series. It is frequently used in the diagnosis of various cognitive and neurological disorders in EEG (Electroencephalography) analysis. Volume conduction effects of various uncorrelated sources present in the brain can produce biased estimates into the estimated values of cross-bicoherence function. Previous studies have discussed volume conduction effects on coherence function which is used to measure linear relationship between EEG signals in terms of their phase and amplitude. However, volume conduction effect on cross-bicoherence analysis which is quite a different technique has not been investigated up to now to the best of our knowledge. This study is divided into two major parts, the first part deals with the investigation of VCUS (Volume Conduction effects due to Uncorrelated Sources) characteristics on EEG-cross-bicoherence analysis. The simulated EEG data due to uncorrelated sources present in the brain was used in this part of study. The next part of study is based upon investigating the effects of VCUS on the statistical analysis of results of EEG-based cross-bicoherence analysis. The study provides an important clinical application because most of studies based on EEG cross-bicoherence analysis have avoided the issue of VCUS. The cross-bicoherence analysis was performed by detecting the change in MSCB (Magnitude Square Cross-Bicoherence Function) between EEG activities of change detection and no-change detection trials. The real EEG signals were used which were recorded from 15 healthy subjects performing the visual modified delayed matching-to-sample paradigm experiment. The results obtained showed the significant effects of VCUS on the statistical analysis of the results for comparatively short inter-electrode spacing less than the 4cm.